Urgensi untuk Membangun Sikap Positif Ibu Nifas dalam Pemberian Kolostrum pada Bayi Baru Lahir - Sari, Rury Narulita; Hardika, Mufida Dian; Sundari, Sundari; Ulfa, Maria (FORUM ILMIAH KESEHATAN, 2023)
Colostrum, the first breast milk that comes out, contains immune substances and has high nutritional value, but there are still postpartum mothers who do not have a positive attitude towards the use of colostrum. So research was needed that aimed to describe the characteristics of postpartum mothers' attitudes regarding giving colostrum to newborn babies. Researchers used descriptive research, involving 32 postpartum mothers at the Independent Practice of Midwife Ny. Sudarsih, Winongo, Madiun. Data regarding the attitudes of postpartum mothers was obtained using an instrument in the form of a questionnaire which was also equipped with questions about the characteristics of the respondents. The data that had been collected was then analyzed using descriptive statistical methods in the form of frequency and percentage diagrams and tables. From the results of the analysis, it was found that the largest age group was 20-35 years (68.75%), the largest parity group was 2 or more children (53.12%), the most education was secondary level (46.88%), the largest occupation was as a housewife (56.25%). Meanwhile, the distribution of attitudes is positive = 65.62%, neutral = 12.5% and negative attitudes = 21.88%. Furthermore, it could be interpreted that there are still many postpartum mothers who did not have a positive attitude towards the use of colostrum, namely 3438%. It was concluded that the attitude of postpartum mothers regarding the use of colostrum still needs to be developed.Keywords: colostrum; postpartum; attitude ABSTRAK Kolostrum sebagai air susu ibu yang keluar pertama kali mengandung zat kekebalan serta bernilai gizi tinggi, namun masih ada ibu nifas yang belum bersikap positif terhadap pemanfaatan kolostrum. Maka diperlukan penelitian yang bertujuan untuk mendeskripsikan karakteristik sikap ibu nifas tentang pemberian kolostrum pada bayi baru lahir. Peneliti menggunakan jenis penelitian deskriptif, yang melibatkan 32 ibu nifas di Praktik Mandiri Bidan Ny. Sudarsih, Winongo, Madiun. Data tentang sikap ibu nifas diperoleh dengan menggunakan instrumen berupa kuesioner yang juga dilengkapi dengan pertanyaan tentang karakteristik responden. Data yang telah dikumpulkan selanjutnya dianalisis menggunakan metode statistika deskriptif berupa diagram dan tabel frekuensi dan persentase. Dari hasil analisis didapatkan bahwa kelompok umur terbanyak adalah 20-35 tahun (68,75%), kelompok paritas terbanyak adalah 2 anak atau lebih (53,12%), pendidikan terbanyak adalah level menengah (46,88%), pekerjaan terbanyak adalah sebagai ibu rumah tangga (56,25%). Sementara itu, distribusi sikap adalah positif = 65,62%, netral = 12,5% dan sikap negatif = 21,88%. Selanjutnya dapat diinterpretasikan bahwa masih banyak ibu nifas yang belum bersikap positif terhadap pemanfaatan kolostrum yaitu 3438%. Disimpulkan bahwa sikap ibu nifas tentang pemanfaatan kolostrum masih perlu dibangun.Kata kunci: kolostrum; nifas; sikap